(untitled) (Revista de Ciências Agroveterinárias, 2020)
Wood, due to its organic constitution, is highly susceptible to biodeterioration agents, making preservative treatment essential to those with low natural durability. Currently, the main products used in the preservative treatment of wood are CCA and CCB, which because of their constitution, are toxic to the environment and human health. Faced with this situation, it is essential to develop studies on natural products that have a biocidal action and thus can be used in the wood treatment, giving greater protection and increasing the lifespan of the piece. Considering this perspective, the present study aims to assess the quality (penetration and retention) and the efficiency of natural preservatives applied to the treatment of Araucaria angustifolia, Eucalyptus viminalis, and Pinus taeda, subjected to accelerated rotting under laboratory conditions. The woods of the three species were submitted to preservative treatment with tannin, tall oil, and neem oil, using the cold quick immersion method at the concentration of 5% of the product preservative solution for five minutes. In the sequence, they were assessed by the accelerated rotting test under the action of rotting fungi Trametes versicolor and Gloeophyllum trabeum, following the recommendations of ASTM D 2017 (2005) and ASTM D 1413 (1999). Based on the results, it was observed that P. taeda wood showed the best penetration to the neem and tall oil preservatives. The tannin presented vascular penetration for the three species. The best retention values were from A. angustifolia and P. taeda, for all treatments applied. Regarding the efficiency, comparing the results found for the other species, all treatments were efficient for P. taeda wood when in contact with the brown rot fungi (G. trabeum).